PELAKSANAAN PROGRAM PENDIDIKAN DAN PELATIHAN (DIKLAT) OLEH BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) PROVINSI RIAU TAHUN 2016 - M. Agung Maulana; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Professional development of the State Civil Apparatus (ASN) is one of the national agendas in the utilization of government apparatus in improving the quality and development of the ASN, Diklat has an important role to help improve ASN's capabilities and competencies. Apparatus Resources have a very strategic position in the organization, meaning ASN plays an important role in carrying out activities to achieve better government goals.The research objective was to find out the education and training program that had been carried out by the Riau Province Human Resources Development Agency (BPSDM) in the improvement and development of the State Civil Apparatus in 2016. The type of research used was Descriptive Qualitative. The location of this study was conducted at the BPSDM Office in Riau Province. The technique of data collection is done by completing information through interviews with informants who are considered competent to support this research and carry out documentation and request the data needed to the agency under study.Research results that show that: (1) The education and training program of BPSDM Riau Province is included in good condition, effective and efficient. This was due to training materials, delivery methods, facilities and infrastructure, widyaswara capacity (speakers), learning process, the proportion of time in delivering the material and the method of organizing training felt by the training participants as well. (2) Quality of Human Resources produced by BPSDM Riau Province experienced an increase based on exposure from informants related to improving the quality of ASN. Keyword :Education and training,BPSDM Province of Riau